The relevance of non-axiality and low-lying excited states for slow magnetic relaxation in pentagonal-bipyramidal erbium(III) complexes probed by high-frequency EPR - Arneth, Jan Victor; Spillecke, Lena; Koo, Changhyun; Bazhenova, Tamara A.; Yagubskii, Eduard B.; Klingeler, Rüdiger (Chemistry - a European journal, 2025)
High-frequency/high-field electron paramagnetic resonance studies on a series of seven-coordinate pentagonal-bipyramidal (PBP) erbium(III) complexes Er(DAPMBH/H2DAPS)X (H2DAPMBH = 2,6-diacetylpyridine bis-4-methoxy benzoylhydrazone, H4DAPS = 2,6-diacetylpyridine bis-(salicylhydrazone)) demonstrate the effects of different apical ligands (X = (H2O)Cl (1), (CH3OH)N3 (2), Cl2 (3)) on the local magnetic anisotropy of the central ErIII ions. In particular, we report direct experimental determination of the effective g-values and zero field splittings of the energetically low-lying Kramers doublets. Our quantitative determination of the magnetic anisotropy highlights the relevance of an axial g-tensor for SMM behavior and suggests that fast magnetic relaxation is mainly driven by a thermally assisted quantum tunnelling process via low-lying excited states.